2022
DOI: 10.4236/ae.2022.102010
|View full text |Cite
|
Sign up to set email alerts
|

Ecology, Distribution and Risk of Transmission of Viral Haemorrhagic Fevers by <i>Aedes</i> Mosquitoes around the Port Areas of Tema in Southern Ghana

Abstract: Aedes-borne diseases remain a public health challenge for many countries globally. The extent of spread of invasive species of Aedes mosquitoes and risk of transmission of the diseases especially around the point of entry of goods such as ports is not well known in Ghana. This study investigated the ecology, distribution and risk of transmission of viral haemorrhagic fevers by How to cite this paper: Ojukwu, K.C.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The most abundant species of the Aedes mosquito recorded in both populations was Aedes aegypti . This correlates with other studies in Ghana that have found Aedes aegypti to be the most predominant (15,23). The high abundance of these vectors in the country have been attributed to the presence of water holding containers close to human dwellings serving as breeding sites for these mosquitoes.…”
Section: Discussionsupporting
confidence: 91%
“…The most abundant species of the Aedes mosquito recorded in both populations was Aedes aegypti . This correlates with other studies in Ghana that have found Aedes aegypti to be the most predominant (15,23). The high abundance of these vectors in the country have been attributed to the presence of water holding containers close to human dwellings serving as breeding sites for these mosquitoes.…”
Section: Discussionsupporting
confidence: 91%
“…Mosquitoes are considered as the number one enemies of mankind [1]. They are responsible of numerous vector-borne diseases namely malaria, yellow fever, dengue fever, rift valley fever, west Nile virus, Venezuelan equine encephalitis, Japanese encephalitis, Zika, la Crosse encephalitis and chikungunya [2] [3].…”
Section: Introductionmentioning
confidence: 99%
“…Larviciding and IGRs are the options of first choice because the immature stages of mosquitoes are easily managed and controlled [8]. The larvae breed in a series of water-holding containers which included disposed plastic basins, car tyres, plastic containers, buckets, earthenware pots, plastic barrels, metal drums, jerry cans and poly tank [3]. Synthetic mosquito larvicides like pyrethroids, organochlorides, organophosphates and carbamates or insect growth regulators such as chitin synthesis inhibitors and juvenoids proved their undoubted effectiveness against different mosquito species [8].…”
Section: Introductionmentioning
confidence: 99%